Efeitos da atrazina e do duodecil sulfato de sódio sobre a estabilidade de eritrócitos humanos - Fonseca, Lúbia Cristina (2010)
CHAPTER II: This work evaluated the in vitro influence of albumin on the stability of human erythrocytes against the herbicide atrazine present in a commercially available preparation. The sigmoidally shaped curves, observed for the dependence between absorbance at 540 nm and the atrazine concentration in 9 g/L NaCl solution, were characterized by the midpoint (D50) and amplitude of the transition (dD). Incorporation of 1 g/L bovine serum albumin (BSA) shifted the lysis transition of human erythrocytes to the right, with increases in D50 and dD. Above 25 g/L BSA, the lysis transition lost its sigmoidally-shaped nature and assumed a linear dependence with increase in the atrazine concentration. Light microscopy evaluations showed that incorporation of BSA was also associated to formation of a crystalline precipitate that is probably atrazine. The hydrophobic binding sites of albumin are surely responsible for the protective effect of this protein, with removal of the detergent used in the formulation of the product and attenuation of the cooperative nature of hemolysis. However, even with supplementation of albumin, a linear transition of hemolysis also occurs with increasing concentration of atrazine. CHAPTER III: The stability of human erythrocytes against sodium dodecyl sulphate (SDS) was assessed spectrophotometrically in the presence of different concentrations of bovine serum albumin (BSA) and at different temperatures (27-45 °C). The absorbance at 540 nm (A540) was correlated with the concentration of SDS by sigmoidal regression, based on the Boltzmann equation. The erythrocyte stability was characterized by the concentration of SDS that promoted 50% of hemolysis (D50). Progressive increases in the concentration of albumin promoted increases in D50. The BSA concentrations that protected erythrocytes against lysis didn t altered its spectral characteristics. The protective effect of BSA against hemolysis by SDS was attributed to binding of surfactant to the hydrophobic binding sites of this protein. The values of D50 decreased sigmoidally with the temperature increase. This trend, which was not explained by changes in the spectral properties of hemoglobin, may be the result of heterogeneity in the population of erythrocytes.